Corrosion of Brass Fishing Vessel Propeller in Artificial Seawater - Yaqin Rizqi Ilmal; Siahaan Juniawan Preston; Priharanto Yuniar Endri; Demeianto Bobby; Tumpu Mula; Abrori Muhammad Zaki Latif; Priyambodo Bambang Hari (Majalah Ilmiah Pengkajian Industri, 2022)
The propeller was an important component in the fishing vessels marine propulsion system. Brass was widely used as a fishing vessel propeller. Brass was chosen because it has good mechanical properties and good corrosion resistance. The content of seawater in Indonesia has levels of 3% – 3.5% NaCl. In addition to the level of Ion Cl-, environmental factors can affect corrosion rate of material or metal. The environmental factors that affect the corrosion rate are the level of salinity, pH, DO, temperature and TDS. The objective of the present work was to explain the corrosion rate of brass in artificial seawater in Indonesia with exposure time. The material used for research is fishing vessel propeller commercial in Indonesia market. Measurement of the corrosion rate of brass used the principle of weight loss according to ASTM G31-72 (2004). During the corrosion test, the artificial seawater solution was tested for its pH and salinity quality over time of immersion. The result of immersion brass in the artificial seawater shows that the corrosion rate decreases in 1-to-10-days exposure time due to the increase in salinity levels above 30‰. While the results of exposure time immersion above 15 days tends to increase the corrosion rate due to a decrease in pH level. pH level of seawater depends on the environmental conditions and tends not to change significantly. Keyword: Artificial Seawater, Brass,  Corrosion Rat, pH, Salinity.